Influence of spirituality, religiosity and multicultural competency on trainee counselors’ self-efficacy in dealing with legal and ethical issues among private university students - Subarimaniam, Neerushah (2018)
Spirituality, religiosity, and multicultural competency help trainee counselors to navigate the challenges of being professional helpers. The evolution and integration of spirituality, religiosity, and multicultural competency have been mushrooming in a number of research fields. Spirituality is the sense of interconnectedness with the Supreme Being and religiosity is defined as community and cultural beliefs that involves practices, rituals, and validation from a group of people. Multicultural competency is one’s awareness, knowledge, and skills about various cultures. The purpose of this research is to examine the influence of spirituality, religiosity, and multicultural competency on trainee counselors’ self-efficacy in dealing with legal and ethical issues. A total of 148 respondents from three private universities in Malaysia participated in the research through simple random cluster sampling. There were a total of four instruments used to measure spirituality, religiosity, multicultural competency, and self-efficacy in dealing with legal and ethical issues respectively. Data were analyzed using Pearson Correlation followed by Multiple Regression. Correlation analysis revealed that there is a positive relationship between spirituality and self-efficacy in dealing with legal and ethical issues (r = 0.241, p < .05), religiosity and self-efficacy in dealing with legal and ethical issues (r = 0.163, p < .05), and multicultural competency and self-efficacy in dealing with legal and ethical issues (r = 0.418, p < .05). However, the r value of the correlation analysis between spirituality and selfefficacy in dealing with legal and ethical issues shows low correlation. On the other hand, the strength of relationship between religiosity and self-efficacy in dealing with legal and ethical issues is negligible. While the coefficient of r value between multicultural competency and self-efficacy in dealing with legal and ethical issues reflects a substantial relationship. Next, the researcher performed multiple regression and the analysis revealed that all three independent variables which are spirituality [F (3, 144) = 17.9, p = .004], religiosity [F (3, 144) = 17.9, p = .007], and multicultural competency [F (3, 144) = 17.9, p = .000] influenced trainee counselors’ self-efficacy in dealing with legal and ethical issues. Multicultural competency, (β = 0.452) has the strongest influence on trainee counselors’ self-efficacy in dealing with legal and ethical issues followed by spirituality, (β = 0.210) and religiosity, (β = 0.199). The findings showed the importance of spirituality, religiosity, and multicultural competency on improving trainee counselors’ self-efficacy in dealing with legal and ethical issues. Hence, this research is vital as it provides the idea of incorporating spirituality, religiosity, and multicultural competency in the process of shaping the trainee counselors who eventually would be competent in dealing with legal and ethical issues in counseling profession.